PENGARUH JOB ENRICHMENT TERHADAP MOTIVASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL PADA PT. NUTRIFOOD INDONESIA SURABAYA - Ongkowidjojo, Andreas (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Motivation can be improved through various ways, among others is how to give job enrichment on his employees. Job enrichment could also improve satisfaction and commitment to the company. By giving enough responsibility on employees, the employees will feel more satisfied because his work gained recognition. Job enrichment gave some advantage as more employees feel satisfied customers are satisfied with the ministry, reduce employment, employee beyond capacity and reducing the errors committed employees. reduce the work of employees who exceed the capacity, and reduce employee error. This research aims to examine the influence of job's of motivation, job satisfaction and organizational commitment on employee PT. Nutrifood Indonesia Surabaya. In this research that is worn is research conclusive in the study of experimental or causal research. The sampling techniques used is non probability of sampling. A kind of methods used is purposive of sampling. The sample used amounted to 106 employees of PT. Nutrifood Indonesia Surabaya. Data collected by using a questionnaire. Analytical techniques used are simple linear regression analysis with the help of the program SPSS. The results of this analysis indicate that the job's influence positively and significantly to employee motivation, job satisfaction and organizational commitment.